The pursuit of philosophy : some Cambridge perspectives - Papazoglou, Alexis (Malden, MA : Wiley-Blackwell, 2012)
Eleven Cambridge academics approach philosophy from various fields, to broaden its practical and theoretical applications. Guides a tour through various academic departments-including history, political science, classics, law, and English-to ferret out the philosophy in their syllabi, and to show philosophy's symbiotic relationship with other fields. Provides a map of what philosophy is considered to be at Cambridge in the early twenty-first century, about a hundred years after the "founding fathers" of analytic philosophy reigned at Cambridge. Offers useful new directions for the study and application of philosophy, and how other fields can influence them.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: University of Cambridge. -- Faculty of Philosophy; University of Cambridge. -- Faculty of Philosophy; Philosophy, British -- 20th century; Philosophy, English -- 20th century; Philosophy -- Study and teaching (Higher) -- England -- Cambridge; PHILOSOPHY -- History & Surveys -- Modern; Electronic books; Electronic books